KARAKTERISTIK CAKE BERAS RENDAH LEMAK DENGAN PENGGUNAAN PROPORSI GUM XANTHAN DAN NATRIUM KARBOKSIMETIL SELULOSA (Na-CMC) - Joyowiguina, Petrina; Sutedja, Anita Maya; Widjajaseputra, Anna Ingani (Jurnal Teknologi Pangan dan Gizi, 2014)
Fat content in rice Cake is 16,84% theoretically. The understanding of healthy living encourages people to reduce the amount of fat in food. Kidney beans can be used as a fat replacer. Rice Cake can be made with the addition of Na-CMC 4% and margarine substitutes by kidney beans for up to 100%. The addition of xanthan gum in combination with NaCMC will be studied to solved the rice Cake dryness. The proportion of gum xanthan and Na-CMC added to low fat rice Cake dough for 4% of the weight of rice flour. Research using a non factorial randomized block design with the treatment is proportion gum xanthan and Na-CMC 0%:100%; 10%:90%; 20%:80%; 30%:70%; 40%:60%; and 50%:50% with four replication. The proportion of xanthan gum and Na-CMC provides a significant effect on physicochemical tests that include moisture content, specific volume, hardness, cohesiveness, gumminess, chewiness at Î± = 5% and organoleptic tests that include, pore uniformity, ease beaten, softness and ease of swallow (moistness) but no significant effect (Î± = 5%) to a taste. Treatment of fat reducing which most accepted was combination of xanthan gum and Na-CMC 20%: 80%.